Existence of Educational Personnel in Create Transparency Reporting Education Financing at Informatics Vocational School Integrated Bandung - H. Soro , Suharyanto; Susanti, Ai Citra; Sariningsih, Nur Endah (Civiliza Publishing, Indonesia., 2025)
Financing education is vital components in organization education quality , but implementation transparency reporting Still face various challenges in the era of decentralization Education . Research This aiming to study existence power education in create transparency reporting financing education at Informatics Vocational School Integrated Bandung. Using approach qualitative descriptive , data collected through observation , interview in-depth , and study documentation . Research results show power education play a role strategic through mechanism structural with implementation transparency realized through display information finance and ARKAS applications . Research This also reveals factor Supporter in the form of framework regulation , support leadership , and implementation technology information , while factor inhibitor covers delay disbursement of funds and limitations infrastructure technology . Research This confirm importance strengthening capacity power education and optimization technology information For increase transparency reporting financing in schools vocational that has complexity more tall in management finance Because need development skills vocational